Merespons Perubahan: Peran Kritis Kepemimpinan Wanita dalam Membangun Masa Depan Islam - Muchlisin (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2024)
This study aims to answer the question of how women's leadership in Banyuwangi can play a role in responding to changes in the times, especially in the context of social and political developments. In addition, this study will also examine how Islamic values ​​can be used as a basis for building more inclusive and progressive leadership, and its impact on regional development. This study uses a qualitative approach with a case study to analyze the role of women's leadership in Banyuwangi. Data were obtained through observation, interviews with the community, local officials, political activists, and workers, as well as policy documentation. The analysis process includes data reduction, data display, and data verification to identify patterns of roles and impacts of women's leadership. The analysis methods used are content analysis, discourse, and interpretation to explore the meaning of policies, public perceptions, and the contribution of women's leadership to social development and the future of Islam. The results of this study indicate that women's leadership has an important role in facing changes in the Islamic world, by providing a more inclusive perspective and encouraging social progress and sustainable education. The results of the study underline the importance of gender equality in leadership positions to create faster and more inclusive change. The contribution of this study updates the perspective on women's leadership in Islam and introduces a new approach to Islamic leadership theory that emphasizes gender equality. However, this study has limitations in terms of geographical coverage and methodology, so further research with a quantitative approach and wider sample is needed for a deeper understanding.